PERSEPSI GURU TERHADAP GAYA BELAJAR SISWA DAN PENERAPAN PEMBELAJARAN BERDIFERENSIASI DI SEKOLAH DASAR - Ziyad A wahyudi; Arfan T Prahamadya; Suherli Kusmana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Teachers' understanding of students' learning styles is an essential component of effective teaching practice, particularly in elementary schools that exhibit highly diverse learning characteristics. Nevertheless, accommodating multiple learning styles within a single classroom still faces a number of obstacles, ranging from limited instructional time and inadequate facilities to high teacher-student ratios. This study aims to uncover teachers' perceptions of students' learning styles, the teaching adjustment strategies they apply, and the obstacles they encounter at SDN 2 Ender. The study employed a descriptive qualitative approach involving six classroom teachers from grades I to V, selected through purposive sampling. Data were collected through in-depth interviews, classroom observation, and documentation study, then analyzed through the stages of data reduction, data display, and conclusion drawing, with data validity ensured through source and method triangulation. The findings show that all six teachers held a consistent conceptual understanding of visual, auditory, and kinesthetic learning styles and believed that such understanding is essential for effective learning. Observation was the most widely used method for identifying learning styles, while the visual style was identified as the most dominant, followed by the kinesthetic style in lower grades. Teachers had implemented differentiated learning with a relatively standardized set of strategies, although implementation remained constrained by limited time, facilities, and high student ratios. The study concludes that teachers' conceptual readiness and creativity have not been fully matched by adequate structural support, making the strengthening of training, the equitable distribution of identification instruments, and the provision of facilities and a more proportional teacher-student ratio the key recommendations for improving the quality of differentiated learning in elementary schools.